1996
DOI: 10.1074/jbc.271.51.33105
|View full text |Cite
|
Sign up to set email alerts
|

Switching Amino-terminal Cytoplasmic Domains of α(1,2)Fucosyltransferase and α(1,3)Galactosyltransferase Alters the Expression of H Substance and Galα(1,3)Gal

Abstract: When ␣(1,2)fucosyltransferase cDNA is expressed in cells that normally express large amounts of the terminal carbohydrate Gal␣(1,3)Gal, and therefore the ␣(1,3)galactosyltransferase (GT), the Gal␣(1,3)Gal almost disappears, indicating that the presence of the ␣(1,2)fucosyltransferase (HT) gene/enzyme alters the synthesis of Gal␣(1,3)Gal. A possible mechanism to account for these findings is enzyme location within the Golgi apparatus. We examined the effect of Golgi localization by exchanging the cytoplasmic ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 32 publications
1
40
0
Order By: Relevance
“…15 This was proposed to be because the Gal(␤1,4)GlcNAc-R substrate is common to ␣1,2FT and ␣1,3GT and due to the earlier location of ␣1,2FT within the glycosylation modification pathway in the Golgi. 16 We therefore examined endogenous ␣1,2FT expression by flow cytometry using FITC-conjugated UEA-I lectin to detect Fuc(␣1,2)Gal. Both ECV304 and EAhy926 were positive, while melanoma, TE671 and HT1080 cells were negative (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…15 This was proposed to be because the Gal(␤1,4)GlcNAc-R substrate is common to ␣1,2FT and ␣1,3GT and due to the earlier location of ␣1,2FT within the glycosylation modification pathway in the Golgi. 16 We therefore examined endogenous ␣1,2FT expression by flow cytometry using FITC-conjugated UEA-I lectin to detect Fuc(␣1,2)Gal. Both ECV304 and EAhy926 were positive, while melanoma, TE671 and HT1080 cells were negative (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Several groups have shown that the catalytic domains of glycosyltransferases can be replaced with heterologous proteins, such as GFP, without detriment to proper Golgi localization (41). Likewise, the exchange of localization domains between different glycosyltransferases has yielded active proteins whose location within the Golgi depends on the origin of the localization domain, attesting to the modularity of the protein (35,36,69,70).…”
Section: Generation Of Cell Lines Stably Expressing Fluorescent Protementioning
confidence: 99%
“…We confirmed this by transient transfection of the GlcNAc6ST-3-EYFP-expressing CHO cells with the gene encoding GlyCAM-1 fused to a human immunoglobulin G heavy chain (GlyCAM-IgG). The secreted molecule was isolated using protein A-Sepharose, and enzyme activity was determined by incorporation of 35 S-labeled sulfate into the glycoprotein. As shown in Fig.…”
Section: Generation Of Cell Lines Stably Expressing Fluorescent Protementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, switching the cytoplasmic tails of these transferases altered the dominant effect of FT indicating that the cytoplasmic tail affects the localization sites of the enzymes (17).…”
mentioning
confidence: 99%